Fueling the Ffire of calling: a multilevel analysis of the effects of transformational leadership on self-concordance at work and living a calling - Yuchao Pan (Acta Psychologica)
In career development, the pursuit of the deep integration of work and personal interests, values, and passions has become the career dream of numerous human beings. Drawing on the self-concept theory of career development, this study proposes that transformational leadership promotes self-concordance at work, which in turn contributes to living a calling. With a sample of 333 medical personnel nested in 49 work units, the idea was tested with multilevel analyses. The results showed that leaders' transformational leadership was positively related to self-concordance at work among both followers and leaders themselves. Furthermore, self-concordance at work was positively associated with living a calling among followers and leaders. Based on these results, theoretical and practical implications, as well as directions for future research, are discussed.